Sensitivity analysis of bicycle characteristics for pavement roughness monitoring by vibration data - Ghaderi, O.; Cafiso, S.; Caponnetto, R.; Pappalardo, G. (Journal of Science and Cycling, 2024)
Introduction Promoting cycling, both as a mode of transport and as an integrating element of other forms of urban mobility, is a key part of making cities sustainable. Vibration caused by lack of pavement maintenance affects the comfort, health and safety of cyclists and has been identified as one of the main infrastructural barriers to cycling. The focus of this paper is to investigate how the physical characteristics of bicycles affect the vibration response under different pavement conditions, and to explore the potential of crowdsourced collection with sensor-equipped bicycles to collect data for road condition and comfort assessment of micro-mobility users.